Douglas Kinnard - SJSU Special Collections & Archives::::::::: (2022)
Douglas Kinnard attended San Jose State College from 1934-1935. At SJSC, he was active in sports including shotput and track. He was also a member of Phi Mu Alpha, a men's music honor fraternity, and directed the Little Symphony Orchestra in a student recital. After leaving SJSC, he returned in 1939 to perform as a bass player as part of Johnny Cooper's Orchestra.